Place the indicated product in the proper location on the grid.
(4a + x)(a - x)

Question

Asked 2/28/2013 9:44:59 AM

Updated 5/7/2015 7:40:06 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [5/7/2015 7:33:28 AM]

andrewpallarca|Points 19974|

andrewpallarca|Points 19974|

Question

Asked 2/28/2013 9:44:59 AM

Updated 5/7/2015 7:40:06 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [5/7/2015 7:33:28 AM]

Rating

3

(4a + x)(a - x)

= 4a^2 + ax - 4ax - x^2

= 4a^2 + ax - 4ax - x^2

Added 5/7/2015 7:33:08 AM

3

(x + 2)(x - 2)

= x^2 + 2x - 2x - 4

= x^2 - 4

= x^2 + 2x - 2x - 4

= x^2 - 4

Added 5/7/2015 7:34:21 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/7/2015 7:37:34 AM]

3

(4a + x)(a - x)

=4a^2 - 4ax + ax - x^2

=4a^2 - 3ax - x^2

=4a^2 - 4ax + ax - x^2

=4a^2 - 3ax - x^2

Added 5/7/2015 7:37:25 AM

This answer has been confirmed as correct and helpful.

3

(2x - y)(4x^2 + 2xy + y^2)

= 8x^3 - 4x^2y + 4x^2y - 2xy^2 + 2xy^2 - y^3

= 8x^3 - y^3

= 8x^3 - 4x^2y + 4x^2y - 2xy^2 + 2xy^2 - y^3

= 8x^3 - y^3

Added 5/7/2015 7:40:06 AM

27,102,470

questions answered

There are no comments.